Anthracycline-induced cardiotoxicity : the role of proteolytic pathways - Sishi, Balindiwe J. N. (Balindiwe Jennifer Nonkosazana) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.